Hand hygiene behavior in a tertiary university hospital: differences between surgical and nonsurgical departments. Issue 1 (December 2015) - G., Sendlhofer; Krause, R.; Kober, B.; K., Vander; Zierler, R.; Brunner, G.; Augustin, T.; Stelzl, L.; Kamolz, L.
Abstract Background Health care-associated infections are a major patient safety issue worldwide. Hand hygiene (HH) campaigns have started all over the world to increase awareness and decrease HH barriers. The aim of this study was to assess healthcare professionals' HH-knowledge, HH-barriers as well HH-environmental factors in general and especially in surgical and nonsurgical departments within a tertiary university hospital. Methods In order to achieve our primary goal, five phases were implemented: i) environmental audit, ii) baseline survey, iii) HH-campaign, iv) follow-up survey and v) alcohol-based hand rub consumption. Results The environmental audits showed that 443 HH-dispensers were missing. A total of 1, 340 questionnaires were returned (baseline: 855; follow-up: 485). Eight HH-barriers were addressed in the baseline survey, 2 of which became significantly reduced during the HH-campaign. HH-environment improved and was followed by a significant increase in compliance with respect to the five moments for HH. Progress in the surgical departments was more evident than in nonsurgical departments. The average procurement of alcohol-based hand rub rose from 105 to 108 mL per patient day in intensive care units and from 26 to 31 mL per patient day in wards. Conclusion HH-motivation can be addressed with comprehensive HH-campaigns; however, positive role models are needed to attract all healthcare professionals to take part. The necessity of physicians taking part in HH-campaign is the key to the future success of HH-campaigns.